Algebraic theory of automata and languages - Itō, Masami, 1941- (World Scientific, 2004)
Although there are some books dealing with algebraic theory ofautomata, their contents consist mainly of Krohn-Rhodes theory andrelated topics. The topics in the present book are ratherdifferent. For example, automorphism groups of automata and thepartially ordered sets of automata are systematicallydiscussed. Moreover, some operations on languages and special classesof regular languages associated with deterministic andnondeterministic directable automata are dealt with. The book isself-contained and hence does not require any knowledge of automataand formal languages.